Adverse events in apheresis: An update of the WAA registry data. Issue 1 (February 2016) - Mörtzell Henriksson, M.; Newman, E.; Witt, V.; Derfler, K.; Leitner, G.; Eloot, S.; Dhondt, A.; Deeren, D.; Rock, G.; Ptak, J.; Blaha, M.; Lanska, M.; et al.
Abstract: Apheresis with different procedures and devices are used for a variety of indications that may have different adverse events (AEs). The aim of this study was to clarify the extent and possible reasons of various side effects based on data from a multinational registry. The WAA-apheresis registry data focus on adverse events in a total of 50846 procedures in 7142 patients (42% women). AEs were graded as mild, moderate (need for medication), severe (interruption due to the AE) or death (due to AE). More AEs occurred during the first procedures versus subsequent (8.4 and 5.5%, respectively). AEs were mild in 2.4% (due to access 54%, device 7%, hypotension 15%, tingling 8%), moderate in 3% (tingling 58%, urticaria 15%, hypotension 10%, nausea 3%), and severe in 0.4% of procedures (syncope/hypotension 32%, urticaria 17%, chills/fever 8%, arrhythmia/asystole 4.5%, nausea/vomiting 4%). Hypotension was most common if albumin was used as the replacement fluid, and urticaria when plasma was used. Arrhythmia occurred to similar extents when using plasma or albumin as replacement. In 64% of procedures with bronchospasm, plasma was part of the replacement fluid used. Severe AEs are rare. Although most reactions are mild and moderate, several side effects may be critical for the patient. We present side effects in relation to the procedures and suggest that safety is increased by regular vital sign measurements, cardiac monitoring and by having emergency equipment nearby.